The impact of neighborhood environment and social interaction on the health of Chinese residents: empirical analysis from CGSS 2021 - Wang, Dongliang; Li, Huanjun; Liu, Ping (Frontiers in Public Health, 2025)
BackgroundThe neighborhood environment plays a crucial role in shaping residents’ health and quality of life.MethodsBased on 2021 Chinese General Social Survey (CGSS 2021), we used multiple linear regression model to conduct regression analysis and mediation analysis, focusing on the relationship among neighborhood environment, social interaction and residents’ health. Our sample size is 8148 people, including 3679 men and 4469 women, 5412 in urban areas and 2736 in rural areas, the mean age was 54.64 years.ResultsWe find that the mean score of Chinese residents’ health is 2.88, which is above the medium level, and the neighborhood environment, social environment and physical environment have significant positive effects on the health of residents. Social interaction plays a mediating role in the mechanism of social environment on residents’ health, whereas it plays a moderating role in the relationship between the physical environment and health. Distinctions in health outcomes are observed between urban and rural residents as well as between individuals institutional/non-institution employment, highlighting the influence of social environment disparities.ConclusionOur research underscores the importance of improving neighborhood environment, fostering social interaction and implementing inclusive public policies to promote equitable health outcomes.DiscussionFuture research is recommended to explore more refined mechanisms linking neighborhood environment and health through longitudinal designs and experimental interventions.